2018
DOI: 10.1038/s41598-018-31282-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of serum urate concentrations and gout in a high-risk population, patients with chronic kidney disease

Abstract: We evaluated genetics of hyperuricemia and gout, their interaction with kidney function and medication intake in chronic kidney disease (CKD) patients. Genome-wide association studies (GWAS) of urate and gout were performed in 4941 CKD patients in the German Chronic Kidney Disease (GCKD) study. Effect estimates of 26 known urate-associated population-based single nucleotide polymorphisms (SNPs) were examined. Interactions of urate-associated variants with urate-altering medications and clinical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…All participants self-identified as Han Chinese. Previous genetic studies also utilized self-reported gout [ 12 , 76 , 77 ] and demonstrated that self-reporting of physician-diagnosed gout resulted in high sensitivity and precision [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…All participants self-identified as Han Chinese. Previous genetic studies also utilized self-reported gout [ 12 , 76 , 77 ] and demonstrated that self-reporting of physician-diagnosed gout resulted in high sensitivity and precision [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…Biomaterials such as DNA, serum, plasma, and urine are collected using standardized methods to identify biomarkers associated with CVD incidence and CKD progression [ 17 ]. In addition to epidemiological topics such as blood pressure [ 18 ], heart failure [ 19 ], dietary patterns [ 20 ], and gout [ 21 ], biomarkers and genes such as urine 6-bromotryptophan [ 22 ], serum uromodulin [ 23 ], GWAS of urate and gout [ 24 ], telomere length [ 25 ], and other biomarkers and genes have been actively investigated.…”
Section: Representative Non-dialysis-dependent Ckd Cohort Studiesmentioning
confidence: 99%
“…Additionally, since URAT1 is a member of the OATs, and four of them have been localized at the basolateral and luminal areas of the PT, studies have suggested that all of them may mediate urate transport in both the renal secretion and reabsorption. Besides, a renal-specific transporter RST, which is mainly localized at the apical surface of the PT may also contribute to PT urate reabsorption 13,14. Increased oxidative stress and hypovolemia stimulate urate tubular reabsorption, with angiotensin II, epinephrine and insulin hormones acting as potential mediators 15.…”
Section: Creatinine and Uric Acid Renal Tubular Transportmentioning
confidence: 99%